2017
DOI: 10.1016/j.asjsur.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the POSSUM, p-POSSUM, o-POSSUM, and APACHE II scoring systems in predicting postoperative mortality and morbidity in gastric cancer patients

Abstract: The POSSUM scoring system performed well with respect to predicting morbidity risk following gastric cancer resection. For predicting postoperative mortality, p-POSSUM and o-POSSUM exhibited superior performance relative to POSSUM and APACHE II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Various risk scoring systems have been introduced to identify surgical complications, including the American Society of Anesthesiologists (ASA) classification, APACHE (Acute Physiology and Chronic Health Evaluation), and POSSUM (Psychological and Operative Severity Score for the Enumeration of Mortality and Morbidity) [66,68,69]. Hong et al compared the performance of POSSUM and APACHE II scoring systems for predicting surgical morbidity in 612 gastric cancer patients undergoing gastrectomy and found that the rate predicted by POSSUM, 36.6%, was close to the actual rate of 34% [70]. However, these scoring systems have limitations, such as interobserver variation (ASA), complexity (APACHE), and overestimation of mortality in lower risk groups (POSSUM).…”
Section: Integrative Risk Modelsmentioning
confidence: 99%
“…Various risk scoring systems have been introduced to identify surgical complications, including the American Society of Anesthesiologists (ASA) classification, APACHE (Acute Physiology and Chronic Health Evaluation), and POSSUM (Psychological and Operative Severity Score for the Enumeration of Mortality and Morbidity) [66,68,69]. Hong et al compared the performance of POSSUM and APACHE II scoring systems for predicting surgical morbidity in 612 gastric cancer patients undergoing gastrectomy and found that the rate predicted by POSSUM, 36.6%, was close to the actual rate of 34% [70]. However, these scoring systems have limitations, such as interobserver variation (ASA), complexity (APACHE), and overestimation of mortality in lower risk groups (POSSUM).…”
Section: Integrative Risk Modelsmentioning
confidence: 99%
“…Postoperative morbidity and mortality rates are objective measures of outcomes that can be used to modify behavior and assess the quality of care. Previous studies have evidenced the important role of the POSSUM system as a predictor of postoperative morbidity and mortality 5,9,10 . A systematic review of the literature that evaluated POSSUM and its variants in patients undergoing surgery for colorectal cancer showed that the POSSUM score was able to predict morbidity in a reliable way and the P-POSSUM was the most accurate predictor of mortality, even when compared with CR-POSSUM 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The widely adopted POSSUM score is generally used by surgeons to evaluate postoperative complications and risk of mortality within 30 days after major operations such as macrovascular surgery, gastric cancer surgery, colorectal surgery, thoracic surgery and joint replacement 26. The POSSUM score has been evaluated in numerous studies, and its modifications have been recognised as highly effective for surgical audit purposes.…”
Section: Methodsmentioning
confidence: 99%